Local Authority of Bugis Oral Literary “Caritana Andi Sessu” and its Emforcement in the Perspective of Character Education - Rudi Karma; Muhlis Muhlis (Journal of Indonesian Language Education and Literary, 2019)
Literary learning is a series of learning that integrated with the teaching of Indonesian and it was taught at all educational levels.  The common problem is the lack of learning materials related to literature in the form of stories which are the local wisdom of local students, especially in Wajo Regency. Whereas the existence of these folklore in the community has always existed which incarnated into various forms of oral literature such as Folk song. This study is a qualitative research with data that is the focus of research is the classic Bugis story (literature) contained in the singing of the Buginese people's Pakkacapi. The objective and urgency of the research in this study is the existence of Pakkacapi which has very rarely made the existence of a classic Bugis story contained in it also endangered. Data collection techniques used are interview and documentation techniques as well as data analysis techniques by doing repeated readings that focus full attention on the elements that provide an overview of the local wisdom of the Bugis community contained in the text. The results of this study are (1) Bugis song “Ceritana Andi Sessu” contains forms of local wisdom in it even though there is an implied directly depicted and some are not directly described. (2) The elements of local wisdom basically have accommodated and become part of the values of character education (3) The values of local wisdom in the story of Andi Sessu are in accordance with or relevant to the values of religious character education, honest, loving the motherland, responsible, democratic, nationalism, respect for achievement, and social care. (4). The application of "Andi Sessu's story " as a literary learning material in schools can only be applied at the Middle School and Senior High School levels with the assistance of teachers at the Junior High School level.